Socio-Cultural Change and Business Ethics in Post-Soviet Countries: The Cases of Belarus and Estonia - Rees, Christopher J. (Journal of business ethics, 2009)
The aim of this literature-based study is to explore the influence of socio-cultural factors on business ethics in post-soviet countries with dissimilar cultural contexts. Specifically, this article seeks to identify and compare contextual influences on informal norms of morality in business in transitional post-soviet societies. In order to pursue this investigation, the countries of Belarus and Estonia were identified as being among the most noteworthy examples of culturally different post-soviet countries in transition. The study reveals contradictory manifestations of mixtures of business norms in both Estonia and Belarus, which are conditioned by the merger of an autocratic bureaucratic soviet system with more participative and empowering forms of western management. The most persistent changes relate to moves from patriarchal and paternalistic types of relationship and low work motivation. The significance of these differences, which include nationality and religious legacies, will almost inevitably be overlooked should the countries be placed under the general umbrella of ‘former soviet states’ when considering business ethics in these contexts.